Effect of Cold Storage Time (4°C) on Malondialdehyde (MDA) Level, Motility and Viability Spermatozoa of Cyprinus carpio L. Punten Strain - Wirastuti, Rosyi; Marhendra, Agung Pramana Warih; Souhaly, Jantje Wiliem; Rahayu, Sri (Graduate School, Universitas Brawijaya, 2020)
The aim of this research is to know the level of MDA, motility, and viability spermatozoa of C. carpio L. in cold storage time at 4°C. This study used treatment extenders that were NaCl 0.9% as control, diluent of egg yolk with concentrate 0%, 5%, 10%, 15%, and storage in 0 h, 24 h, 48 h, 72 h, and 96 h at 4°C. The data were analyzed using ANOVA (P<0.05). The results showed that the quality (motility and viability) of spermatozoa C. carpio L. punten strain in cold storage could be maintained at 96 h. The optimum storage for motility was found in diluent of egg yolk concentrate 5% at 48 h. MDA levels of semen from C. carpio L. Punten strains after being stored at cold temperatures increased at 0 h to 24 h, then decreased after 48 h of storage and increase at 72 h - 96 h stored. Egg yolk concentration and storage time had a significant effect on MDA levels. There is a negative correlation between MDA levels and motility. There was no correlation between MDA levels and the viability of spermatozoa C. carpio L. punten strain. Keywords: C. carpio L, Egg yolk, Malondialdehyde, Motiliy, Viability